Antioxidant activities of curry leaves (Murayya koeniigi) and salam leaves (Eugenia polyantha) - Novi Safriani; Normalina Arpi; Novia Mehra Erfiza; Rini Ariani Basyamfar (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
This study aimed to extract the active antioxidant compounds from curry leaves (Murayya koeniigi) and salam leaves (Eugenia polyantha) using three types of solvent; water, ethanol (50%) and hexane, and determine the total polyphenols contents, activity of free radicals scavenging using DPPH (1,1-diphenyl-2-picrylhydrazyl) and ferric reducing power of the extract of those materials. The result showed that curry leaves extracted using water contain a higher amount of polyphenols than other solvent extracts, while for the salam leaves, ethanol (50%) extracts give a higher polyphenol content than others. Total polyphenols extracts had a positive correlation with antioxidant activity in both DPPH radical scavenging and ferric reducing power. Extracts that contain a high amount of polyphenols also exhibit high antioxidant activity. The result indicated that the polarity level of the solvent will determine extraction result and its antioxidant activity